Mathematical model of terrorism population dynamics: a case of a community under the attack of two terrorists groups - Atokolo ∗†, W.; Aja ‡, R.O.; Omale, D.; Paul, R.V. (International Journal of Mathematical Analysis and Modelling, 2023)
We formulated in this work, a mathematical model which is made up of system of non-linear ordinary dierential equations that is analyzed so to study the dynamics of terrorism, a case of a community under the attack of two terrorists groups. The basic terrorism multiplication number (M0) was computed after which we investigated the existence of Terrorism Free Equilibrium point (TFE) which was investigated to be locally and globally aymptotically stable whenever (M0) < 1 and (M0) > 1 respectively. A unique equilibrium point known as, Terrorism Persistent Equilibrium point (TPE) was also investigated to exist whenever(M0) > 1. Sensitivity analysis of the basic terrorism multiplication number (M0) was then carried out to see the impacts of some parameters to the growth of terrorism in a population. Results show that, the rate at which individuals are exposed to terrorists group two and the rate at which terrorists in group one are recruited into terrorists group two represented by (w) and (1) respectively are the most sensitive parameters that increase terrorism in a population, as an increase in the parameter values reduces the value of the basic terrorism multiplication number (M0) to a value less than unity. The obtained mathematical result implies that, the terrorists group two (T2) has a mighty negative effect on the growth of terrorism in a population. Finally, numerical simulation was performed which results were in conformity with our analytical results.